2019
DOI: 10.24821/resital.v20i2.2459
|View full text |Cite
|
Sign up to set email alerts
|

Pola Permainan Alat Musik Keroncong dan Tenor di Orkes Keroncong Irama Jakarta

Abstract: The Musical Pattern of Keroncong and Tenor Instruments in the Keroncong Irama Orchestra Jakarta. This study discusses the musical pattern of keroncong and tenor instruments and their application to the songs "Cente Manis" and "Sambel Cobek". Both of these instruments are the identity of the Jakarta style of keroncong. The study was conducted with a descriptive qualitative approach. The data was collected through observation, interviews, and documentation. Based on the results of the study, it was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…Keroncong music repertoire has experienced a setback since the 1980s, the following table explains the setbacks in keroncong song production as below: Based on the table 1, it is proven that in the 80s to this day keroncong has suffered a setback in song production there is no sound at all of the new songs being produced. The present performance or recording of keroncong is merely a repetition of the keroncong song repertoire before the 80s, and only a kind of klangenan as if the representation of the powerlessness of keroncong music competes with other types of music in the music industry scene [19]. Therefore, this research will seek to find the right formulation in adding the keroncong song repertoire, namely through the ideas and ideals of today's generation of students who know and understand what forms of keroncong can be accepted by Indonesian young generation because they are the culprit.…”
Section: Resultsmentioning
confidence: 99%
“…Keroncong music repertoire has experienced a setback since the 1980s, the following table explains the setbacks in keroncong song production as below: Based on the table 1, it is proven that in the 80s to this day keroncong has suffered a setback in song production there is no sound at all of the new songs being produced. The present performance or recording of keroncong is merely a repetition of the keroncong song repertoire before the 80s, and only a kind of klangenan as if the representation of the powerlessness of keroncong music competes with other types of music in the music industry scene [19]. Therefore, this research will seek to find the right formulation in adding the keroncong song repertoire, namely through the ideas and ideals of today's generation of students who know and understand what forms of keroncong can be accepted by Indonesian young generation because they are the culprit.…”
Section: Resultsmentioning
confidence: 99%
“…These data have been compared based on previous writings and also oral data from witnesses who were used as informants by the researcher. It can be concluded that in addition to the authenticity of the data, there has never been any research examining the development of the keroncong orchestra of young people from 2010 to 2019, the relevant research on this is a dissertation study entitled "Reconstruction of Young Keroncong Music in Bandung City" [6]. However, this research looks at the young people of Bandung constructing their ideas from time to time, very holistically.…”
Section: Resultsmentioning
confidence: 99%
“…The cuk and cak may be called in various terms in some Keroncong music. In Keroncong Tugu, for instance, they are called prounga and machina (Ganap, 2011), while in Keroncong Jakarta, they are called 'Keroncong' and 'tenor' (Supiarza, Setiawan, & Sobarna, 2019). Keroncong is divided into some kinds, which are resulted from the hybrid process (Ganap, 2000).…”
Section: Composingmentioning
confidence: 99%